Handbook of research on modern optimization algorithms and applications in engineering and economics - Vasant, Pandian 1961-; Weber, Gerhard-Wilhelm 1960-; Vo Ngoc Dieu 1971- (Engineering Science Reference, an imprint of IGI Global, 2016)
"This book highlights the latest research innovations and applications of algorithms designed for optimization applications within the fields of engineering, IT, and economics, focusing on a variety of methods and systems as well as practical examples"...
E-Book auf der IGI-Global-Plattform für Käufer der Druck-Ausgabe kostenfrei und zeitlich unbegrenzt zugänglich
Keywords: Mathematical optimization; Algorithms; Optimierung; Algorithmus